Dampak Self-Efficacy Terhadap Kemampuan Pemecahan Masalah Matematika Siswa SD di Bimbel Cerdas Ceria Brebes - Nungki, Nungki Anditiasari (Caruban: Jurnal Ilmiah Ilmu Pendidikan Dasar, 2025)
This study aims to analyze the impact of self-efficacy on improving the mathematical problem-solving skills of 4th-grade elementary school students at Bimbel Cerdas Ceria Brebes. Self-efficacy is the belief in one’s own ability to solve problems. Mathematical problem-solving ability is a high-level skill that is crucial for students and can be influenced by their level of self-efficacy. This research uses a quantitative approach with a correlational method involving 25 fourth-grade students at Bimbel Cerdas Ceria Brebes. Data were obtained through a mathematical problem-solving test and a self-efficacy questionnaire, then analyzed using normality test, linearity test, regression, and correlation analysis. The results show a positive relationship between self-efficacy and mathematical problem-solving skills, with a determination coefficient of 61.5%, indicating that the higher the students' self-efficacy, the better their ability to solve mathematical problems. Therefore, strengthening students' self-efficacy is an important factor in supporting their success in solving problems, especially challenging mathematical problems.